Characterization of Beta-Lactam Resistome of Escherichia coli Causing Nosocomial Infections - Rosalino Vázquez-López; Tanya Hernández-Martínez; Selene Ivonne Larios-Fernández; Celia Piña-Leyva; Manuel Lara-Lozano; Tayde Guerrero-González; Javier Martínez-Bautista; Eduardo Gómez-Conde; Juan Antonio González-Barrios (MDPI AG, 2023)
Nosocomial infections caused by Escherichia coli pose significant therapeutic challenges due to the high expression of genes encoding antimicrobial drug resistance. In this study, we investigated the conformation of the beta-lactam resistome responsible for the specific pattern of resistance against beta-lactam antibiotics. A total of 218 Escherichia coli strains were isolated from in-hospital patients diagnosed with nosocomial infections, obtained from various sources such as urine (n = 49, 22.48%), vaginal discharge (n = 46, 21.10%), catheter tips (n = 14, 6.42%), blood (n = 13, 5.96%), feces (n = 12, 5.50%), sputum (n = 11, 5.05%), biopsies (n = 8, 3.67%), cerebrospinal fluid (n = 2, 0.92%) and other unspecified discharges (n = 63, 28.90%). To characterize the beta-lactam resistome, all strains were subjected to antibiotic dilution tests and grown in beta-lactam antibiotics supplemented with Luria culture medium. Subsequently, multiplex PCR and next-generation sequencing were conducted. The results show a multi-drug-resistance phenotype, particularly against beta-lactam drugs. The primary determinant of this resistance was the expression of the blaTEM gene family, with 209 positive strains (95.87%) expressing it as a single gene (n = 47, 21.6%) or in combination with other genes. Common combinations included blaTEM + blaCTX (n = 42, 19.3%), blaTEM + blaCTX + blaSHV (n = 13, 6%) and blaTEM + blaCTX + blaBIL (n = 12, 5.5%), among others. The beta-lactam resistome of nosocomial Escherichia coli strains isolated from inpatients at the "October first" Regional Hospital of ISSSTE was predominantly composed of members of the blaTEM gene family, expressed in various configurations along with different members of other beta-lactamase gene families.